Officers of the American Society for Testing Materials (ASTM) Committee E-14 on Mass Spectrometry - Fireside Studio (1963)
Group photograph of the officers of the American Society for Testing and Materials (ASTM) E-14 on Mass Spectrometry taken at a conference in San Francisco. Present from left are Norman D. Coggeshall (Vice Chair, Program); R.E. Fox (Chairman); Andrew Gans "Jack" Sharkey, Jr. (Vice Chair, Arrangements); and Henry Earle Lumpkin (Secretary and Treasurer). In 1952, a group of mass spectrometrists petitioned the American Society for Testing and Materials (ASTM) for the creation of a committee specifically on mass spectrometry and allied topics. The committee, which became known as ASTM E-14, was a precursor to the American Society for Mass Spectrometry (ASMS), which was subsequently organized in 1969.
Keywords: American Society for Testing and Materials; Mass spectrometry; Lumpkin, Henry Earle, 1920-; Congresses and conventions; Portraits, Group